2016
DOI: 10.1016/j.cherd.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating the non-similarity in local holdups of spouted beds obtained by CT with scale-up methodology based on dimensionless groups

Abstract: The common scale-up methodology for gas-solid spouted bed that has been reported in the literature is based on matching dimensionless groups. This methodology has been validated by measuring global hydrodynamic parameters and non-validated by limited point measurements of solids holdup and velocity. Therefore, the purpose of this work is to implement our advanced non-invasive gamma-ray computed tomography (CT) technique to assess and to demonstrate that the reported set of the dimensionless groups are not adeq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 47 publications
6
22
0
Order By: Relevance
“…The gas flow rates were measured using the two rotameters and gas flow was introduced into the spouted beds through the inlet orifice (gas distributor). To maintain stable spouting in spouted beds, the conditions of the experiments used in [13] were followed.…”
Section: Experimental Work 21 Spouted Beds Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…The gas flow rates were measured using the two rotameters and gas flow was introduced into the spouted beds through the inlet orifice (gas distributor). To maintain stable spouting in spouted beds, the conditions of the experiments used in [13] were followed.…”
Section: Experimental Work 21 Spouted Beds Setupmentioning
confidence: 99%
“…Recently, Ali et al [13] studied the local solids and gas holdup distributions along the bed height using gamma-ray computed tomography (CT) technique which measures time averaged crosssectional distribution of phases densities and hence holdups. Also, Aradhya [14] investigated the local solids holdup and velocity in spouted beds using sophisticated and newly developed optical fiber probes which measure the point measurements of both solids velocity and solids concentrations (holdups with a proper calibration).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The kinetic model using these parameters conducted to relative errors of 3.25 % and 3.98 % for HDS and HDN conversion when compared with experimental values (which had the highest error margin of 0.3 wt%).…”
Section: Theorymentioning
confidence: 99%
“…In our previous work, we implemented a study comparing columns with different relations between length and diameter (L R /D R ) and reactor diameter to pellet diameter ( N = D R /d P ). It was observed that to ensure a similar hydrodynamic behaviour inside two packed columns of different dimensions, the liquid holdups between both columns should be equalized . This kind of equality, combined with a model that incorporates a rigorous description of the void fraction of the bed and considers an adequate closure for the interfacial momentum exchange model (IMEM), has led to predictions of pressure drops with an error that is down to 1.9 %, which implies a 50 % improvement in holdup predictions and up to 5 times better accuracy in pressure drops.…”
Section: Introductionmentioning
confidence: 99%